A new insight on the effects of iron oxides and dissimilated metal-reducing bacteria on CH4 emissions in constructed wetland matrix systems. Issue 6 (January 2021) - Cheng, Shiyi; Qin, Congli; Xie, Huijun; Wang, Wenxing; Hu, Zhen; Liang, Shuang; Feng, Kuishuang
Graphical abstract: Highlights: Iron oxides as constructed wetland matrix reduced CH4 emissions. Iron oxides with or without DMRB both showed multiple effects on CH4 emissions. Iron oxides increased the relative abundance of methanogens and Geobacter. Iron oxides promoted AOM and competed with methanogens in the presence of DMRB. Abstract: Iron oxides and dissimilated metal-reducing bacteria (DMRB) have been reported to result in a reduction in methane (CH4 ) emissions in constructed wetlands (CWs), but their mechanisms on CH4 production and oxidation remains unclear. Here, a set of CW matrix systems (Control, Fe-CWs, and FeB-CWs) was established to analyze the CH4 emission reduction from various angles, including the valencies of iron, microbial community structure and enzyme activity. The results revealed that the addition of iron oxides promoted the electron transfer between methanogens and Geobacter to promote CH4 production, but it was interesting that iron oxides also reduced the enzymes involved in the carbon dioxide (CO2 ) reduction pathway and promoted the enzymes that participated in anaerobic oxidation of methane (AOM) thereby leading to the overall reduction in CH4 emissions. Moreover, DMRB could promote iron reduction thereby further reducing CH4 emissions by promoting AOM and competing with methanogens for organic substrates.